Investigating vocabulary retention in English Language learners: A focus on frequency and teaching methods - Gantari, Anissa (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Nahdlatul Ulama Blitar, 2024)
This study aims to investigate the factors that influence vocabulary retention in English language learners, focusing on word frequency and the teaching methods employed. While much research emphasizes the importance of vocabulary frequency in language acquisition, this study explores how frequency interacts with the teaching techniques used by instructors to introduce and reinforce new vocabulary. Through a qualitative analysis of English language classrooms at the elementary school level, the study finds that although frequently taught vocabulary has an impact on student comprehension, teaching methods that involve varied approaches and contextual word usage are more effective in supporting long-term retention. The study suggests that task-based methods, communicative activities, and contextual repetition enhance students' memory of taught vocabulary. These findings provide valuable contributions to English language teaching, particularly in developing more effective teaching strategies to improve vocabulary mastery in second language learners.